مساهمة وظائف الإدارة الرياضية في تحسين تسيير المنشآت الرياضية: دراسة ميدانية أجريت على بعض المركبات الرياضية لولاية البويرة - عز الدين، رامي; بعوش، خالد (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2016)
هدفت الدراسة إلى إبراز مساهمة الإدارة الرياضية في تحسين تسيير المنشآت الرياضية، حيث أجرى الباحث دراسته على عينة قوامها (30) إداريا موزعين على ثلاث (03) منشآت رياضية (مركبات رياضية) تم اختيارها بطريقة عشوائية من المجتمع الأصلي والبالغ ( 14 ) مركبا رياضيا أي ما يقارب نسبة (%20)، وقد انتهج الباحث المنهج الوصفي من خلال توزيع استمارات استبيان على الإداريين، لأخذ آرائهم ووجهات نظرهم حول الموضوع والاستفادة من إجاباتهم في أغراض علمية بحتة، وتم التأكد من صدق الأداة المستخدمة (الاستبيان) بالاعتماد على الصدق الظاهري (المحكمين)، واستخدام النسب المئوية (%) واختبار كا 2، كوسائل إحصائية لتحليل نتائج الدراسة. وفي الأخير أسفرت نتائج الدراسة عن صحة الفرضيات المقترحة وكشفت المساهمة الكبيرة والمميزة للإدارة الرياضية وجميع وظائفها بما في ذلك التخطيط والتنظيم والرقابة في تحسين تسيير المنشآت الرياضية، وعليه أوصى الباحث بتكوين الإطارات في مجال التسيير والإدارة، وتشجيع الأفكار المفيدة لتحسين التسيير النابعة في الأفراد العاملين في المنشأة الرياضية وعلى كافة المستويات، كذلك تسطير برامج تضمن وضع آليات واضحة المعالم تستند إلى منهجية علمية بحتة تأخذ بعين الاعتبار جميع العوائق التي تعيق تسيير المنشآت، بالإضافة إلى زيادة الاهتمام بالعنصر البشري داخل المنشآت الرياضية.
The study aimed to highlight the contribution of sports administration in improving the management of sports facilities, where the researcher conducted a study on a sample of (30) administratively divided into three (03) Sports facilities have been selected at random from the original community Who is(14) a compound mathematically any nearly proportion (20%), has pursued a researcher descriptive approach through the distribution of questionnaires to the administrators, to take the opinions and views on the subject and take advantage of their answers in purely scientific purposes, it was confirmed the veracity of the tool used (questionnaire), depending on the virtual honesty (arbitrators ), the use of percentages (%), test ch2, as a means of statistical analysis of the results of the study . In the latter it resulted in the results of the study about the health of the proposed hypotheses and revealed a large and distinctive contribution to sports management and all its functions including planning, organization and control to improve the management of sports facilities, and the researcher recommended the composition of tires in the area of governance, and to encourage new ideas useful for improving governance stemming in personnel sports facility and at all levels, as well as underline the work programs to ensure well-defined mechanisms based on purely scientific methodology that takes into account all the obstacles and causes that hinder the conduct of installations, as well as increased attention to the human element within the sports facilities.
Keywords: المنشآت الرياضية -- الإدارة الرياضية -- التسيير الإداري